Autotaxin and lysophosphatidic acid1 receptor-mediated demyelination of dorsal root fibers by sciatic nerve injury and intrathecal lysophosphatidylcholine - Aoki Junken; Niwa Masami; Ueda Mutsumi; yano Ryo; Matsushita Yosuke; Uchida Hitoshi; Nagai Jun; Chun Jerold; Ueda Hiroshi (SAGE Publishing, 2010)
Abstract Background Although neuropathic pain is frequently observed in demyelinating diseases such as Guillain-Barré syndrome and multiple sclerosis, the molecular basis for the relationship between demyelination and neuropathic pain behaviors is poorly understood. Previously, we found that lysophosphatidic acid receptor (LPA1) signaling initiates sciatic nerve injury-induced neuropathic pain and demyelination. Results In the present study, we have demonstrated that sciatic nerve injury induces marked demyelination accompanied by myelin-associated glycoprotein (MAG) down-regulation and damage of Schwann cell partitioning of C-fiber-containing Remak bundles in the sciatic nerve and dorsal root, but not in the spinal nerve. Demyelination, MAG down-regulation and Remak bundle damage in the dorsal root were abolished in LPA1 receptor-deficient (Lpar1-/-) mice, but these alterations were not observed in sciatic nerve. However, LPA-induced demyelination in ex vivo experiments was observed in the sciatic nerve, spinal nerve and dorsal root, all which express LPA1 transcript and protein. Nerve injury-induced dorsal root demyelination was markedly attenuated in mice heterozygous for autotaxin (atx+/-), which converts lysophosphatidylcholine (LPC) to LPA. Although the addition of LPC to ex vivo cultures of dorsal root fibers in the presence of recombinant ATX caused potent demyelination, it had no significant effect in the absence of ATX. On the other hand, intrathecal injection of LPC caused potent dorsal root demyelination, which was markedly attenuated or abolished in atx+/- or Lpar1-/- mice. Conclusions These results suggest that LPA, which is converted from LPC by ATX, activates LPA1 receptors and induces dorsal root demyelination following nerve injury, which causes neuropathic pain.